Use of ustekinumab after other biological therapies in moderate-severe psoriasis: Real long-term data - Manuel David Gil-Sierra; Esmeralda Ríos-Sánchez; María del Pilar Briceño-Casado (Farmacia Hospitalaria)
Objective: Ustekinumab is used in moderate-severe plaque psoriasis with inadequate response to anti- tumour necrosis factor α drugs. Recent studies support the need to assess real long-term data. The aim of this study was to evaluate the real long-term effectiveness and safety of ustekinumab in moderate-severe plaque psoriasis refractory to 2 anti-tumour necrosis factor α drugs. Method: Retrospective descriptive study from January 2010 to March 2019. The study included patients with moderate-severe plaque psoriasis previously treated with at least 2 anti-tumour necrosis factor α biologic drugs. The effectiveness endpoints were Psoriasis Area and Severity Index 90 and 75 response rates at weeks 24, 48, 72, and 96. Safety was assessed using adverse effects and treatment withdrawal. Results: A total of 36 patients were included (men, 61%). Ustekinumab was used after treatment with 2 anti- tumour necrosis factor α drugs in 88.9% of patients. The biologic drugs most frequently administered prior to ustekinumab were infliximab (94.4%) and etanercept (91.7%). It was observed that at least 66.7% of patients reached Psoriasis Area and Severity Index 90 at weeks 24, 48, 72, and 96. Adverse effects were recorded in 6 patients. There were no treatment withdrawals. Conclusions: Ustekinumab showed real long-term effectiveness and safety in moderate-severe plaque psoriasis with inadequate response to 2 previous anti- tumour necrosis factor α drugs.